2016
DOI: 10.11604/pamj.2016.25.5.6616
|View full text |Cite
|
Sign up to set email alerts
|

Prolonged neuromuscular block in a preeclamptic patient induced by magnesium sulfate

Abstract: Recent large use of magnesium in the obstetric population should incite anesthesiologists to control its side effects and drugs interactions. We report a case of a 30-year-old woman, with severe preeclampsia and HELLP syndrome, receiving sulfate magnesium and nicardipine, who underwent a cesarean section under general anesthesia. She developed a prolonged and deep neuromuscular blockade, which was antagonized three hours later with neostigmine. In case of therapeutic hypermagnesaemia, non-depolarizing relaxant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 12 publications
(12 reference statements)
0
11
0
Order By: Relevance
“…By contrast, one study reported no clinically significant interaction between magnesium sulfate and calcium-antagonists among women with suspected preeclampsia, particularly with respect to neuromuscular weakness or other serious magnesium sulfate-related adverse effects [8]. In another study, in a woman receiving magnesium sulfate and a calcium-antagonist and undergoing C-section under general anesthesia, prolonged and deep neuromuscular blockade induced by vecuronium (6 mg) was antagonized 3 h later with neostigmine [7].…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…By contrast, one study reported no clinically significant interaction between magnesium sulfate and calcium-antagonists among women with suspected preeclampsia, particularly with respect to neuromuscular weakness or other serious magnesium sulfate-related adverse effects [8]. In another study, in a woman receiving magnesium sulfate and a calcium-antagonist and undergoing C-section under general anesthesia, prolonged and deep neuromuscular blockade induced by vecuronium (6 mg) was antagonized 3 h later with neostigmine [7].…”
Section: Discussionmentioning
confidence: 96%
“…Pre-treatment with magnesium sulfate 40 mg/kg was observed to not significantly affect the recovery time of moderate neuromuscular blockade facilitated by sugammadex [6]. Combination of magnesium sulfate with a calcium-antagonist in patients undergoing C-section under general anesthesia may or may not prolong the neuromuscular blockade [7,8].…”
Section: Introductionmentioning
confidence: 89%
“…Magnesium reduces muscle contraction in proportion to its concentration in the blood and accelerates the effects of NMBDs [ 68 69 ]. In contrast, calcium increases ACh release while maintaining action potential at the neuromuscular junction [ 70 ].…”
Section: Factors That Affect Muscle Contractilitymentioning
confidence: 99%
“…Moreover, it prevents progression to eclampsia, and it is recommended as the treatment of choice for seizures. 4 , 12 Doses used in this scenario increase the risk of hypermagnesemia, and consequently muscle relaxant interaction is more likely, especially in this population who is already more sensitive to these drugs. 12 During clinical practice, this drug interaction has not been valued enough in scenarios requiring rapid sequence intubation (obstetrics, e.g.)…”
mentioning
confidence: 99%